PEMANFAATAN BORAKS UNTUK PENGAWETAN BAMBU BETUNG (Dendrocalamus asper Backer) TERHADAP SERANGAN RAYAP TANAH (Captotermes curvignathus) - Nurnaningsih Hamzah; Niken Pujirahayu; Sitti Raslam Tama (Jurnal Ecogreen, 2016)
The aim of the research was to examine the use of borax for preservation on Dendrocalamus asper from termite attack (Captotermes curvignathus) so as to improve the quality of bamboo betung.  The research scheme applied completely randomized design.  Variables were observed in this study is the water content, retention of borax, and weight loss.  Result showed that average moisture content of the bamboo betung is 7,525%, the highest retention at a concentration of 1%, and the lowest weight loss at a concentration of 1%. Keywords: Bamboo betung, borax, retentions